Pengaruh Berkumur dengan Air Kelapa Muda (Coconut Water) terhadap Perubahan Ph Saliva pada Siswa Kelas IV & V Madrasah Ibtidaiyah Al-Khairat Sospol Manado - Ni Made Yuliana; Novarita Mariana Koch; Jeineke Ellen Ratuela; Yenny Lisbeth Siahaan (Journal on Education, 2025)
In the mouth, saliva is a very important element to protect teeth against external influences, as well as from within the oral cavity itself, elementary school children are very vulnerable to dental and oral health. A decrease in salivary pH can cause rapid demineralization of tooth elements, while an increase in pH can lead to bacterial colonization which leads to increased calculus formation. Coconut water contains calcium ions, phosphorus and proteoin, which are the same substances in saliva to help the remineralization process. This study aims to determine the effect of gargling young coconut water on changes in saliva pH in students of class IV & V at Madrasah Ibtidayah Al-Khairat Sospol Manado. This type of research is a quasi-experiment with a one group pre test post test design, which was carried out on 47 samples using the total sampling method. Data collection was obtained from the results of measuring saliva pH using universal pH test paper with criteria 0-14, saliva pH assessment format before and after gargling 30ml of young coconut water (Coconut Water). Data analysis used non-parametric statistical tests with the Wilcoxon test method. Based on analysis using the Wilcoxon test, it shows that there is a significant effect seen from the p value = 0.000 (0.000 < 0.05). This means that there is an effect of gargling young coconut water (Coconut Water) on the pH of saliva.